LEARNING MANAGEMENT HISTORY METHOD AFFECTING ANALYTICAL THINKING ABILITY AND LEARNING ACHIEVEMENT OF GRADE 6 STUDENTS - Namuang, Sasithorn (Journal for Developing the Social and Community, 2023)
The objectives of this research were to (1) improve the effectiveness of learning management with historical methods that affect the ability to think critically according to the 70/70 criteria, (2) study the ability to think critically and manage learning with historical methods, and (3) compare the pre- and post-school achievement of Grade 6 students. Samples used in this research Grade 6 students studying history 13 students 1 classroom Semester 2 of Academic Year 2021 Ban Khu Din Sai School Roi Et Primary Education Area Office District 2 Obtained from Cluster Random Sampling The research tools were 10 learning management plans, 3 subjective critical thinking abilities, 3 questions with difficulty values of 0.30-0.70, classification power values of 0.40-0.90, confidence values of 0.91, conformity index of 0.67-1.00, and 30 multiple-choice pre- and post-learning achievement assessments of 4 choices. The difficulty value is 0.30-0.60, the classification power value is 0.30-1.00, the confidence value is 0.97, and the consistency index is 0.67-1.00. Management of historical methods that affect critical thinking abilities and academic achievement For Grade 6 students, the efficiency was 73.54/75.90, above the required threshold. Students who have been organized learning through historical methods have the ability to think critically. 75.90 percent, which is higher than the threshold. 70 percent required Students who are taught by historical methods have higher post-study achievement than before. statistically significant at the .05 level.